Dark matter, neutrino mass, cutoff for cosmic-ray neutrino, and the Higgs boson invisible decay from a neutrino portal interaction. (April 2019) - Yin 殷, Wen 文
Abstract: We study an effective theory beyond the standard model (SM) where either of the two additional gauge singlets, a Majorana fermion and a real scalar, constitutes all or some fraction of dark matter. In particular, we focus on the masses of the two singlets in the range of (10) MeV- (10) GeV with a neutrino portal interaction, which plays an important role not only in particle physics but also in cosmology and astronomy. We point out that the thermal dark matter abundance can be explained by (co-)annihilation, where the dark matter with a mass greater than 2 GeV can be tested in future lepton colliders, CEPC, ILC, FCC-ee and CLIC, in the light of the Higgs boson invisible decay. When the gauge singlets are lighter than (100) MeV, the interaction can affect the neutrino propagation in the universe due to its annihilation with cosmic background neutrino into the gauge singlets. Although in this case it can not be the dominant dark matter, the singlets are produced by the invisible decay of the Higgs boson at such a rate which is fully within reach of future lepton colliders. In particular, a high energy cutoff of cosmic-ray neutrino, which may account for the non-detection of Greisen-Zatsepin-Kuzmin (GZK) neutrino or the non-observation of the Glashow resonance, can be set. Interestingly, given the cutoff and the mass (range) of WIMPs, a neutrino mass can be " measured" kinematically.